Analisis Pengaruh Struktur Kepemilikan Keluarga terhadap Kinerja Perusahaan: Studi Empiris pada Perusahaan Non Keuangan Terdaftar di Bursa Efek Indonesia Periode 2009-2014 - Septiana, Eva; Dalimunthe, Zuliani; Wasilah, Wasilah (UI Scholars Hub, 2020)
The study aims to analyse how the ownership structure of a family company affects the company’s performance. The company’s performance was measured using Tobin’s Q to see how the market re- sponds to strategies and policies taken by the family company. The study took samples of 147 family companies listed on the Indonesia Stock Exchange during 2009-2014. The results showed that the family company had significantly lower performance compared to non-family companies, but the relationship between ownership by the family is a quadratic in which there is a direction reversal at the 76% ownership rate. The study also found that the company’s performance is lower when the CEO of the family company is managed by the second generation than when administered by the first generation.